La transición energética en costa rica y sus consecuencias, 1911-1929 - Notten, Frank (Revista de historia., 2006)
In this article we determine the causes and consequences of the energy transition from coal to petroleum in Costa Rica during World War I. Through an analysis of a selection of imports between 1911 and 1929 we want to find out if Costa Rica entered the process of economic modernization normally associated with energy transitions.